The Influence of Social Media Marketing, Brand Image, and Influencer Marketing on Purchase Intention at XYZ Restaurant - Kurniawan, Shelvy; Setiadi, Fina Fauzi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
The use of social media in marketing is not only to market products but it can be used to improve the company's image and consumer purchasing interest. XYZ restaurant is engaged in the food & beverage sector by serving typical Indonesian cuisine, they realize the importance of using social media as an efficient marketing tool. The purpose of this study is to determine the influence of social media marketing and influencer marketing on purchase intention and the role of brand image in mediating the influence of social media marketing on purchase intention. The data collection method in this study was by distributing questionnaires. The data analysis method used in this study is SEM. The results of this study indicate that social media marketing has a significant influence on brand image, brand image has a significant influence on purchase intention, influencer marketing has a significant influence on purchase intention, and social media marketing has a significant influence on purchase intention mediated by brand image.